UVC dosage effects on the physico - chemical properties of lime (Citrus aurantifolia) juice - Mohd Hanif, Hani; Shamsudin, Rosnah; Mohd Adzahan, Noranizan (Korean Society of Food Science and Technology, 2016)
Lime juice is in high demand due to a sour taste. Commercial thermal pasteurization extends juice shelf-life; however, fruit juice subjected to thermal pasteurization tends to change color and lose vitamin content. Lime juice was irradiated with ultraviolet-C (UVC) at dosages of 22.76, 30.19, and 44.24 mJ/cm2 to investigate effects on the physicochemical properties of lime juice. pH values of lime juice did not change while total soluble solids, turbidity, titratable acidity, sweetness, and color values of lime juice did change after UV treatments. Changes in quality index indicators were prominent at the highest UV dosage of 44.24 mJ/cm2. A low UVC dosage was effective for treatment of lime juice with minimal changes in juice properties.